Vascularized proximal fibula epiphyseal transfer for distal radius reconstruction in children: A systematic review. Issue 8 (24th October 2015) - Aldekhayel, Salah; Govshievich, Alexander; Neel, Omar Fouda; Luc, Mario
Abstract : Purpose: Reconstruction of the distal radius in children is cumbersome, requiring simultaneous restoration of joint function and axial growth. Vascularized proximal fibular epiphyseal transfers (VFET) have been popularized over non‐vascularized transfers and prosthesis. This systematic review aims to evaluate the effectiveness of VFET and its associated complications. Methods: Electronic database of PubMed MEDLINE was searched between 1970 and 2014. Studies reporting VFET for distal radius reconstruction in children (<15 years old) with clear reporting of technique (vascular pedicle) and objective outcome measures were included. Outcomes of interest were rate of graft growth, bone union and complications. A one‐way Analysis of Variance (ANOVA) test was used to compare growth rates between pedicle types. Results: Fourteen studies met the inclusion criteria, representing 25 patients. Pedicles used were anterior tibial (44%), peroneal (16%), or bi‐pedicled (40%) anastomosed in antegrade (64%) or reverse flow (36%) fashion. Among all pedicle types, best results were achieved using anterior tibial artery with reversed flow, yielding average growth rate of 0.83 cm/year ( P = 0.01). Recipient complications included four premature epiphyseal plate closures, a flap loss, and six wrist radial deviations. Donor complications included six common peroneal nerve palsies (five temporary, a permanent), and a talocalcaneal instability. Overall complication rates between pedicle types were comparable ( P = 0.062). Conclusion: VFET may be a surgical option capable of restoring joint function and axial growth potential in select patients. The reverse flow technique based on the anterior tibial artery may result in superior outcomes. However, the overall complication rate is high and permanent peroneal nerve palsy may result. Level of Evidence: IV © 2015 Wiley Periodicals, Inc. Microsurgery 36:705–711, 2016.